Ways of Knowing, Ways of Being: Exploring a Good Life Through Participatory Audio/Visual Methods with People Labelled with an Intellectual Disability - Boulanger, Josée (Université d'Ottawa / University of Ottawa, 2022)
Purpose and objective: A good life includes opportunities to practice self-determination, to participate in and contribute to society, to have meaningful relationships, and opportunities for self-development as well as physical, emotional, and financial health and security (Verdugo et al., 2012). People labelled with an intellectual disability (PLWID) have had limited opportunities to experience these good things in life and to share their own perspectives about a good life. The purpose of this study was to learn from PLWID who face significant barriers to communication about what they most value as part of a good life. My research was situated within the sociohistorical context of the province of Ontario. My main research questions were: (1) What is a good life from the perspectives of PLWID who use various forms of augmentative and alternative forms of communication (AAC)? (2) What can we learn from past advocacy efforts? (3) What are the possibilities and limitations of participatory audio/visual methods for enabling PLWID to articulate their vision of a good life? Methods: To explore these research questions, I conducted three separate but related studies. The first study consists of six narratives of intellectual disability advocacy that has taken place in Ontario. A focus group session advised me regarding the choice of narratives to be included in the study. To conduct the second study, I adopted various research methods, including participatory audio/visual methods, inclusive research methods and narrative approaches. I facilitated a series of five workshops for five participants labelled as having an intellectual or developmental disability and facing significant barriers to communication and six supporters living in the Ottawa Region. Combining audio/visual and inclusive methods and drawing from augmentative and alternative communication (AAC), supported decision-making (SDM) and Supported Conversation for Adults with Aphasia (SCA™), participants received assistance to think about a good life. A total of 34 video vignettes communicate participants’ perspectives. Finally, to conduct the third study, I used audio/visual methods to document the participatory process of exploring a good life with participants and their supporters. Results: The results reveal that the desire for assistance to practice autonomy and the desire to contribute to shaping supports and services has been at the heart of intellectual disability advocacy efforts. Further, PLWID value participation and relationships as part of a good life. Participation in arts and sports is especially important as are relationships with family and friends. Results demonstrate that using participatory audio/visual methods combined with strategies drawn from SDM, AAC and SCA™ provide practical assistance to PLWID when thinking about and communicating their visions and ideas of the good. Conclusion and implications: The findings of this research indicate the need to continue exploring methodological approaches that facilitate the participation of PLWID and others who face barriers to communication and cognition in research and beyond. The three studies support a radically individual and relational conceptualization of autonomy and decision-making. As such, they suggest the need to rethink accepted ideas about self-determination, including reasoning and decision-making. Finally, the results support the need for individualized assistance that accommodates each person’s cognitive and communication abilities to enable meaningful participation. They also suggest the need for fundamental systemic changes that begin with practicing equality and forms of radically inclusive democracy in all our relations.
Keywords: Intellectual disability; Developmental disability; Visual methods; Participatory research; Inclusive methods; Alternative and Augmentative Communication; Multimodal methods; Good life; Relational autonomy